1987
DOI: 10.1111/j.1365-2621.1987.tb14045.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated Fatty Acids and Fat in Fish Flesh for Selecting Species for Health Benefits

Abstract: An awareness of the protective roll of n‐3 polyunsaturated fatty acids against development of cardiovascular disease has prompted the promotion of fish consumption. It is assumed that those fish rich in polyunsaturated fat and particularly those having high ratios of n‐3 to n‐6 polyunsaturated fatty acids would confer the most benefit. The total fat and fatty acid compositional data are reported herein for 41 different species of fish that are mostly found in the coastal waters of the Eastern United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
2
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(54 citation statements)
references
References 18 publications
(9 reference statements)
8
42
2
2
Order By: Relevance
“…Fatty acids in fishes are derived from two main sources, namely, biosynthesis and diet (Hearn et al, 1987, Morris et al, 1995, Kamler et al, 2001. Palmitic acid content among the SFA is maximum in big size Koi which is in agreement with earlier report (Kaya et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Fatty acids in fishes are derived from two main sources, namely, biosynthesis and diet (Hearn et al, 1987, Morris et al, 1995, Kamler et al, 2001. Palmitic acid content among the SFA is maximum in big size Koi which is in agreement with earlier report (Kaya et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Silva (1992) observed combined amounts of both fatty acids (EPA and DHA) of 37.73% in the oil of 6DUGLQHOOD DXULWD, a Brazilian sardine. The Japanese sardine oil contained no more than 29% (16.8% EPA and 11.3% DHA) (Kinsella, 1986), while the American sardine oil contained 37.1% (11.3% EPA and 25.8% DHA) (Hearn et al, 1987). Oil extracted from some species of fish is presently used as alimentary supplement to modify the plasma's lipidic profile and to balance the aggregating activity of platelets (Dyerberg et al, 1978;Harris et al, 1983).…”
Section: )Lvk Dqg Ilvk Rlomentioning
confidence: 99%
“…Although it is generally recognized that PUFAs composition may vary among species of fish, little attention has been paid to the PUFAs composition of different species when selecting fish for diets. All fishesare considered to be of similar nutritional value, and selection is chiefly based on availability, freshness, flavour and similar factors [6]. Results of clinical and epidemiological research suggest that eicosapentaenoic (EPA) and docosahexaenoic (DHA) acids, found only in fish and seafood, have extremely beneficial properties for prevention of human coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%